Development of the concept of simulation modeling of the ecological situation based on the theory of self-organization (Transport systems and technologies, 2023)
The article is devoted to the development of a concept of simulation of the environmental situation based on the theory of self-organization. The trend of increasing temperature and sea level due to an increase in the level of greenhouse gases in the Earth’s atmosphere is global. This indicates the need to predict the development of the environmental situation in order to inform the population about possible disasters for preparing people's responses, resettlement planning, psychological adaptation. To predict the environmental situation as a result of accidents and disasters, including in rail transport, an analysis apparatus for possible situations is proposed with the aim of developing recommendations for their prevention. An environmental simulation model based on the theory of self-organization was chosen as the apparatus of research. It is based on the processes of mutually agreed relations, as a result of changes in two species of wildlife (object and environment), leading to the formation of a certain orderliness of these relations. Interaction of this kind occurs in the direction of achieving the existing equilibrium state or the formation of a new balance.
Keywords: simulation model, environmental situation, theory of self-organization, expert assessment, equilibrium state, knowledge base.